Fungsi Tanah Dalam Hubungan Sosial Dan Permohonan Tanah Serta Prosesnya - Huda, Afiful; Ainun Nadhiroh, Laili (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2021)
Land has a very important role in the life of the Indonesian nation and in the implementation of national development which is carried out as a sustainable effort to create a just and prosperous society based on Pancasila and the 1945 Constitution. Therefore, the regulation of control, ownership and use of land needs to be further directed towards increasing ensuring order in the field of land law, land administration, land use, or land and environmental selection, so that legal certainty in the land sector in general can be realized. Building Use and Use Rights as referred to in Chapter II of Law Number 5 of 1960 with Government Regulations. In view of: 1. Article 5 paragraph (2) of the 1945 Constitution; 2. Law Number 28 of 1956 concerning Supervision of Enforcement of Plantation Land Rights (State Gazette of 1956 Number 73, Supplement to State Gazette Number 1125).